Nasal Deviation in Patients With Asymmetric Mandibular Prognathism. Issue 7 (October 2017) - Shin, Young-Min; Lee, Sung-Tak; Nam, Ki-Young; Kwon, Tae-Geon
Abstract : Purpose: This study was aimed to evaluate the nasal deviation in patients with asymmetric mandibular prognathism. Materials and Methods: Thirty-five patients with skeletal class III malocclusion were included in the study. Significant mandibular asymmetry of >4 mm menton deviation in three-dimensional (3D) reformatted cone beam computed tomography images was defined as asymmetry group (n = 20). Patients without mandibular asymmetry served as control group (n = 15). The mandibular asymmetry was evaluated pre- and postoperatively. Results: Nasal tip was significantly shifted to the deviated side of the mandible (short side) in the asymmetry group, as compared to the control group (1.5 ± 0.9 degree, P  < 0.01). Alar base angle (ABA) was significantly narrower in nondeviated side (long side) than in the deviated side in asymmetry group. However, control group showed no bilateral difference in ABA. Correction of deviated mandibular prognathism by isolated mandibular surgery resulted in change in the ABA but not the columella base position or nasal asymmetry. ABA on nondeviated side significantly decreased in proportion to the amount of transverse menton movement by surgery ( r  = −0.560, P  < 0.01). Conclusion: Our results showed that mandibular chin deviation was accompanied by nasal deviation. Isolated mandibular surgery can potentially influence the alar base position on the contralateral side of deviation but not the nasal tip asymmetry. Therefore, clinicians should inform patients preoperatively of the fundamental limitation of mandibular surgery in cases with preexisting nasal asymmetry.